The Impact of Cariogenic Food Consumption on Dental Caries Rates Among Children - Maulidina, Nana; Zuhroh, Diah Fauzia; Widiyawati, Wiwik; Ernawati, Ernawati (Universitas Muhammadiyah Gresik, 2024)
Background: The most well-known dental and oral infection is dental caries. The hard tissues of the teeth, such as enamel, dentin, and cementum, become infected with dental caries over time. Dental caries can cause torment that frustrates everyday exercises, prevents fixation, and might in fact make loss of hunger due trouble biting. This study means to dissect the connection between utilization of cariogenic food varieties and the occurrence of dental caries in youngsters at RA Al-Fattah Gresik. Method: The sort of exploration utilized is logical and observational utilizing a cross sectional plan. The populace was 112 kids and the example utilized was 88 youngsters utilizing basic irregular testing procedures. In this review, the FFQ (Food Recurrence Quotionnaire) survey was utilized. Factual tests use Chi-square. Results: The aftereffects of this study showed that of the 88 respondents who experienced dental caries, there were 37 kids (42.0%) and 49 youngsters (55.7%) ate cariogenic food varieties with elevated degrees of utilization. The Chi-Square test analysis yielded p-values of 0.000 and 0.005 respectively, Conclusion: There is a connection between utilization of cariogenic food varieties and the occurrence of dental caries in youngsters at RA Al-Fattah Gresik. Keywords: Dental Caries, Cariogenic Food